2021
DOI: 10.1134/s0006297921030019
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant SARS-CoV-2 S Protein Binds to Glycans of the Lactosamine Family in vitro

Abstract: Many viruses, beside binding to their main cell target, interact with other molecules that promote virus adhesion to the cell; often, these additional targets are glycans. The main receptor for SARS-CoV-2 is a peptide motif in the ACE2 protein. We studied interaction of the recombinant SARS-CoV-2 spike (S) protein with an array of glycoconjugates, including various sialylated, sulfated, and other glycans, and found that the S protein binds some (but not all) glycans of the lactosamine family. We suggest that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Efforts to quantify these interactions on model sialylated species (for example, 3′-sialyllactose), however, were challenging and revealed weak binding (K d millimolar) 16 . Given this weak binding, it is not surprising that conflicting reports exist for the binding of the RBD to sialylated species by traditional glycan microarray screening 6,17,18 . Beyond acidic glycans, recent work suggests that the RBD mimics a galectin scaffold and can bind blood group A antigens 19 and terminal N-acetylglucosamine moieties (for example, GlcNAcα1-3GalNAcβ) 17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to quantify these interactions on model sialylated species (for example, 3′-sialyllactose), however, were challenging and revealed weak binding (K d millimolar) 16 . Given this weak binding, it is not surprising that conflicting reports exist for the binding of the RBD to sialylated species by traditional glycan microarray screening 6,17,18 . Beyond acidic glycans, recent work suggests that the RBD mimics a galectin scaffold and can bind blood group A antigens 19 and terminal N-acetylglucosamine moieties (for example, GlcNAcα1-3GalNAcβ) 17 .…”
mentioning
confidence: 99%
“…Given this weak binding, it is not surprising that conflicting reports exist for the binding of the RBD to sialylated species by traditional glycan microarray screening 6,17,18 . Beyond acidic glycans, recent work suggests that the RBD mimics a galectin scaffold and can bind blood group A antigens 19 and terminal N-acetylglucosamine moieties (for example, GlcNAcα1-3GalNAcβ) 17 . Moreover, it was recently reported that sialylated N-and O-glycans on ACE2 may play a role in S protein cell binding 20,21 .…”
mentioning
confidence: 99%
“…There is less clear evidence of association of ABO blood groups with severe outcomes of the COVID-19 disease such as acute respiratory distress syndrome, kidney injury, intubation, intensive care unit (ICU) admission, or mortality. Two biochemical studies using glycan arrays and ELISAs demonstrate the binding of SARS-CoV-2 spike protein to A-type HBGAs [135,136]. The molecular basis of SARS-CoV-2 interactions with host HBGAs is unknown and the functional significance remains to be determined.…”
Section: Glycan Interactions For Other Viral Pathogensmentioning
confidence: 99%
“…The authors proposed a mechanism linked to the prevention of optimal interaction between ACE-2, which is sialylated, and the spike protein. However, an alternative explanation is suggested by a different publication [96]. The enhancement of infection after the removal of SA might be mediated by the exposure of lactosamine, which was the top hit of a 'reverse' glycan array performed by the authors.…”
Section: Sars-cov-2 Dependency On Glycansmentioning
confidence: 99%